Factors Affecting Online Hotel Reservation Intention In Malaysia - Amoujani, Efat (2011)
In this study, a total number of 172 completed questionnaires were collected. Data were primarily analyzed by test of reliability and factor analysis to ensure both reliability and validity of utilized variables. Consequently, different analyses including pearson\'s correlation coefficient and multiple regression were conducted. In the final analysis of the study, the role of hotel\'s website features, such as, information quality, sensitivity of content, and time on consumers\' intention for online booking were discussed in detail. Each of these items were measured by their specific indicators that are discussed through next chapters in detail.